THE INFLUENCE OF TASK-BASED LANGUAGE TEACHING (TBLT) AND LEARNING TECHNOLOGY ON SPEAKING SKILL DEVELOPMENT: A LITERATURE REVIEW OF RECENT RESEARCH AND METHODOLOGICAL INNOVATIONS - Fety Surfaifel; Imelda; Rosdiana Mata (Adisam Publisher, 2026)
This literature review analyses the synergistic influence of Task-Based Language Teaching (TBLT) and learning technology on the development of EFL students' speaking skills through a review of the literature. The main findings confirm the superiority of TBLT over traditional methods, with the integration of technology-TBLT strengthening effectiveness through personalisation and real-time interaction in accordance with Interactionist Theory and the Output Hypothesis, identifying methodological gaps such as the lack of longitudinal research in the Indonesian context. The study recommends the adoption of hybrid TBLT-technology in the Merdeka Curriculum through teacher training and culturally relevant task design to optimise speaking proficiency in the digital age.